2022
DOI: 10.1111/jam.15773
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus sp. DU-106 ameliorates type 2 diabetes by modulating gut microbiota in high-fat-fed and streptozotocin-induced mice

Abstract: Aims: Type 2 diabetes (T2D) is a chronic disease that manifests as endocrine and metabolic disorders that seriously threatening public health. This study aimed to investigate the effects of Bacillus sp. DU-106 on anti-diabetic effects and gut microbiota in C57BL/6J mice fed a high-fat diet and streptozotocin-induced T2D.Methods and Results: Bacillus sp. DU-106 was administered to model mice for eight consecutive weeks. Oral administration of Bacillus sp. DU-106 decreased food and water intake and alleviated bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Jing et al reported that the abundance of Allobaculum and Blautia was increased after the supplementation of Bacillus sp. DU-106 and metformin [31]. Indeed, LAB intervention for hypercholesterolemia resulted in the change in different species.…”
Section: Discussionmentioning
confidence: 99%
“…Jing et al reported that the abundance of Allobaculum and Blautia was increased after the supplementation of Bacillus sp. DU-106 and metformin [31]. Indeed, LAB intervention for hypercholesterolemia resulted in the change in different species.…”
Section: Discussionmentioning
confidence: 99%
“…Eight comparable studies reported its significant and positive effects on glucose and lipid metabolic biomarkers based on the wellestablished male C57BL/6J HFD-and STZ-induced T2DM mice, such as FBG, HbA1c, insulin, HOMA-IR, AUC glucose , TC, TG, HDL and LDL (Supporting Information Table S5). [35][36][37][38][39][40][41][42] Although the effects of L. paracasei IMC 502 on HOMA-IR and TC were weaker than that of metformin, its positive effects on the other biomarkers were comparable to that of metformin, possibly suggesting that this probiotic has a potential to improve T2DM and may complement the pharmacological effects of other anti-T2DM medications.…”
Section: Discussionmentioning
confidence: 99%
“…DU-106 was proven to alleviate T2DM by regulating the blood glucose balance and modifying the dysbiosis of the gut microbiota. 26 These findings indicate that probiotics act in a strainspecific manner on the intestinal flora structure and associated glucose metabolism signalling pathways to alleviate T2DM. Hence, using probiotics as adjunctive therapy is becoming a viable approach to relieving T2DM.…”
Section: Introductionmentioning
confidence: 87%